2015
DOI: 10.1039/c5ra04117a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of carbon nanotube/carbon fiber hybrid reinforcement by a two-step aryl diazonium reaction

Abstract: Raw carbon nanotube (CNT)/carbon fiber (CF) hybrids were achieved through a two-step aryl diazonium reaction in mild, eco-friendly conditions. Raman spectra, Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) confirmed the grafting of CNT onto the CF surface. The surface topography and surface free energy of the modified CFs were examined by scanning electron microscopy (SEM), transmission electron microscope (TEM) and dynamic contact angle (DCA) tests, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Here, from a macroscopic view, a unique feature of our CVD process is that the CNTs deposit around the fiber surface uniformly, yielding a very thick layer covering the CF. The thickness of our CNT layer is 2–3 orders of magnitude higher than most of reported hybrid fibers …”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Here, from a macroscopic view, a unique feature of our CVD process is that the CNTs deposit around the fiber surface uniformly, yielding a very thick layer covering the CF. The thickness of our CNT layer is 2–3 orders of magnitude higher than most of reported hybrid fibers …”
mentioning
confidence: 83%
“…Currently, many methods such as solution impregnation, chemical grafting, electrophoretic deposition, and chemical vapor deposition (CVD) have been developed to fabricate CNT‐grafted CF structures . Among these methods, the CVD process is most widely used, which directly grows a layer of CNTs on the CF surface; however, it typically yields short and random CNTs with layer thicknesses of a few to 20 µm . Short CNTs provide very limited contact area with the polymeric matrix, and the small layer thickness is not sufficient to penetrate into surrounding matrix thus generating strong interlocking effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intense peaks close to 3600‐3300 cm −1 may be due to hydroxyl groups stretching vibration of phenolic OH or water . Additionally, the new peaks at around 1518 and 1449 cm −1 are assigned to the stretching vibration of CC arising from substituted aromatic ring . More importantly, the bands at 1637 cm −1 can be very safely attributed to CN stretching vibration in the spectrum of CF‐g‐SLDH, confirming that salicylaldehyde has been successfully grafted onto the fiber surface.…”
Section: Resultsmentioning
confidence: 68%
“…Many researchers found that the most effective way is improving the surface activity of the bers and thus improving the interfacial bonding strength between ber and matrix by ber surface treatments. [12][13][14][15][16][17][18] In these methods, carbon nanotubes (CNTs) directly graing 19 or growing on the surface of ber have been attracting the researcher's interests because it can not only improve the surface activity of the bers and also fundamentally solve the problem of agglomeration of carbon nanotubes. This method shows a lot of advantages compared to other methods.…”
Section: Introductionmentioning
confidence: 99%